2007
DOI: 10.1002/pros.20472
|View full text |Cite
|
Sign up to set email alerts
|

Modulating testosterone stimulated prostate growth by phenethyl isothiocyanate via Sp1 and androgen receptor down‐regulation

Abstract: PEITC modulates the testosterone-influenced growth by repressing Sp1, thus down-regulating AR and proliferation. PEITC from cruciferous vegetables may represent a regulator for hormone-dependent growth of the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Even though we observed a consistent decrease in AR mRNA and CBP in a large number of PTC, FTC and FTA tissues from males and females, Pearson's correlation analysis did not show any statistically significant correlation between the two. Inhibition of Sp1 activity reduces AR expression in LNCaP cell line [77] and in rat prostate [78]. Therefore, decreased Sp1 in PTC, FTC and FTA tissues from women and the significant positive correlation observed between AR mRNA and Sp1 expression pattern in PTC and FTA tissues from women suggest that Sp1 could contribute to the down-regulation of AR in a majority of thyroid tumors in females.…”
Section: Discussionmentioning
confidence: 69%
“…Even though we observed a consistent decrease in AR mRNA and CBP in a large number of PTC, FTC and FTA tissues from males and females, Pearson's correlation analysis did not show any statistically significant correlation between the two. Inhibition of Sp1 activity reduces AR expression in LNCaP cell line [77] and in rat prostate [78]. Therefore, decreased Sp1 in PTC, FTC and FTA tissues from women and the significant positive correlation observed between AR mRNA and Sp1 expression pattern in PTC and FTA tissues from women suggest that Sp1 could contribute to the down-regulation of AR in a majority of thyroid tumors in females.…”
Section: Discussionmentioning
confidence: 69%
“…In the model of testosterone (hormone)-induced prostatic cell growth, PEITC negated the growth via downregulation of androgen receptor (AR) (81). This repression of AR in prostate cancer cells by PEITC is significant in cancer chemoprevention since abnormalities of the AR, such as overexpression, have been postulated to be related to the hormone-independent growth of prostate cancer (81). The question as to how PEITC regulates AR was subsequently investigated.…”
Section: Receptors As Molecular Targets For Peitc and Sfnmentioning
confidence: 99%
“…The question as to how PEITC regulates AR was subsequently investigated. It was found that PEITC mediates dual effects on AR, both at the transcriptional and the post-translational level (81). At the transcriptional level, the AR transcript level was reduced via inhibition of the transcription factor Sp1 (which transactivates AR promoter), and at the post-translational level, AR protein degradation was accelerated (81).…”
Section: Receptors As Molecular Targets For Peitc and Sfnmentioning
confidence: 99%
See 1 more Smart Citation
“…In the testosterone-primed prostates, cellular proliferation was stimulated with a significant increase in the cyclins D1 and E, cdk2 and a decrease in p27. Concomitantly, Rb was inactivated as shown by an increase in Rb phosphorylation (54). Inactivation of Rb leads to enhanced activity of E2F1, thereby activating downstream target DNMT1 transcription.…”
Section: Peitc Inhibits Prostate Tumors and Cgi Methylation Of The Mgmentioning
confidence: 99%